Effect of biochar addition on hydrogen and methane production in two-phase anaerobic digestion of aqueous carbohydrates food waste. (November 2016) - Sunyoto, Nimas M.S.; Zhu, Mingming; Zhang, Zhezi; Zhang, Dongke
Highlights: Two-phase anaerobic digestion of food waste for H2 and CH4 production was studied. Biochar significantly increased maximum production rates of H2 and CH4 . Biochar shortened the lag phases of H2 and CH4 production. Biochar enhanced VFA formation in H2 phase and VFA degradation in CH4 phase. Abstract: Effect of biochar addition on hydrogen and methane production in two-phase anaerobic digestion of aqueous carbohydrates was studied using bench-scale bioreactors. The cultures with biochar additions were placed in 100 ml reactors and incubated at 35 °C and pH 5 for hydrogen production. The residual cultures were then used for methane production, incubated at 35 °C and pH 7. Daily yields of hydrogen and methane and weekly yield of volatile fatty acids (VFA) were measured. The hydrogen and methane production potentials, rate and lag phases of the two phases were analysed using the Gompertz model. The results showed that biochar addition increased the maximum production rates of hydrogen by 32.5% and methane 41.6%, improved hydrogen yield by 31.0% and methane 10.0%, and shortened the lag phases in the two phases by 36.0% and 41.0%, respectively. Biochar addition also enhanced VFA generation during hydrogen production and VFA degradation in methane production.